A política de reconhecimento de saberes do ponto de vista da atividade de trabalho docente na Educação Profissional - Natália Valadares Lima (2019)
This thesis aims to analyze the implementation and development of the Knowledge and Skills Recognition (RSC) policy of teachers of the Career of Basic, Technical and Technological Education (EBTT) working in the Federal Center of Technological Education of Minas Gerais (CEFET-MG), by interrogating the theoretical and methodological assumptions that underlie it. To this end, we question the proposition of evaluation of knowledge of the RSC through the aspects emerging from the analysis of the work activity of two teachers of vocational education working in the Computer Networks course, offered by CEFET-MG. Methodologically, for this research, we performed documentary and bibliographic analyzes, as well as observation of classes, semi-structured and self- confrontation interviews. The analysis of the teaching work is based on the theoretical contributions of the theory of activity of historical-cultural perspective, which relies on the productions of Vygotsky, Leontiev and, currently, is developed by Engeström and his peers; and the ergological approach of work, which has Schwartz as one of its main authors. The approximation between these theoretical fields made it possible to understand the differences in the appropriation and treatment of the notion of activity. In this scope, the activity theory elaborates a conception of activity related to its social, cultural and historical dimensions, proposing an analysis based on the constitution of activity systems. On the other hand, ergology, by basing its assumptions in the distance between the prescribed and the real work, proposes a repositioning of the understanding of such dimensions, due to an approach centered on the micro of the work, in the singular relationship established between the subject and the environment. Thus, the analysis of the teaching work in Professional Education anchored in both currents helps us to highlight the social aspects that influence and permeate the teaching work, as well as the uniqueness of the activity in this professional field, which makes the work a space for mobilization and (re)construction of situated and unique knowledge. To analyze the knowledge constructed and mobilized by teachers in their work activity, we founded our analysis on the idea of expansive learning cycles, proposed by the activity theory, and on the notion of renormalization developed by the ergological approach of work. In this context, the detailed analysis of two situations of the relationship between students and teachers, focused, therefore, towards teaching, explains that the teaching work in the technical disciplines of Vocational and Technological Education mobilizes knowledge related to values and personal and professional experiences. Therefore, based on such analysis, we found that the competent practice of these professionals relates to the technical knowledge constructed before and during the teaching exercise, but also with the knowledge of how to conduct the class; how to organize and rhythm the contents to be taught; be able to consider the most appropriate form of care for each student or group of students; worry about the care of the equipment, the common good and the students; search for ways of updating their knowledge, by conducting researches related to the content to be taught; among others. These are, wherefore, competences that the subjects learned at work, by the conduction of classes, and that escape the evaluation framework in the RSC. Given this, considering the documentary character of the evaluation conducted in the RSC, we conclude that this process of recognition of knowledge ends up ignoring a range of knowledge constructed by teachers during their work activity and that are fundamental to their competent practice in their profession, making it necessary rethink the evaluation process proposed here.